"The Multidisciplinary Chair, Discussing Strategies and Tactics for Success." - Daniel Jorgensen; Pamela Brouillard (Academic Chairpersons Conference Proceedings, 2020)
Participants will discuss specific strategies and tactics that can help in successful leadership of a multidisciplinary department.
Keywords: Multidisciplinary; Strategies; Tactics; Leadership; Success